A new species of Acantholycosa Dahl, 1908 (Araneae: Lycosidae) from the Russian Far East - Omelko, Mikhail M.; Komisarenko, Anatoly A.; Marusik, Yuri M. (Zootaxa, 2016)
Acantholycosa Dahl, 1908 is a relatively large genus, comprising 29 species to date (World Spider Catalog 2015). The genus is well delimited; its members are recognized by having 4–6 pairs of ventral spines at leg I, a wide embolus (sometimes with a spine at its base), apical pocket(s) of epigyne separated from fovea, among other characters (cf. Marusik et al. 2004, 2015). Acantholycosa is the among the better known genera of Holarctic Lycosidae due to several revisions and reviews (Kronestedt & Marusik 2002; Marusik et al. 2004, 2015; Marusik & Logunov 2011; Marusik & Omelko 2011). Most Acantholycosa are known from the Altai-Sayan mountain system (21 species, of which 17 are local endemics) and the Maritime Province of Russia (6 species, three are local endemics). Although the Russian Far East is well studied, an expedition to the previously unstudied Phalaza Mt. in the south part of Maritime Province revealed a new species closely related to A. azarkinae Marusik & Omelko, 2011. The main goal of this paper is to provide detailed description of this new species.